História da Matemática em Atividades de Geometria: uma proposta para a formação inicial de professores - Celestino, Kamila Gonçalves (2020)
This reasearch had as its main goal to investigate which characteristics of the History of Mathematics are evident during an experience with Geometry activities with prospective teachers. The experiment was realized with students from the “Licenciatura” course of the State University of Center-West (UNICENTRO) located in the city of Guarapuava – PR. Three activities were realized with the following topics: squaring the circle, height of the Pyramid of Cheops and Golden ratio, which allowed us to show the students ways to work topics as equivalence of the áreas of planar figures, triangles similarity, ratios and proportion by means of the History of Mathematics. With a view to the proposed objective, we based ourselves in the pedagogical potentialities of the History of Mathematics descibed by Fauvel (1991) apud Miguel et al. (2009) and Miguel and Miorim (2008). We found that the History of Mathematics revealed itself as: source of selection of problems, methodology for the classes in Mathematics and an element that favors the critical thinking and the understanding that the Mathematics was built from the human needs. It was elaborated from the experimented activities, as aneducational product associated to this work, a manual with a scheduleof activities, containing all the commented steps for its application, as well as texts and support materials for the realization of the activities. We hope that this reasearch and the educational product which was formulated can contribute with teachers of the basic levels that wish to insert the History of Mathematics in their classes.